THE INFLUENCE OF PUBLIC RELATIONS MEDIA AND MARKETING MIX FACTORS ON CONSUMERS BUYING BEHAVIOR FOR INTHANIN COFFEE IN BANGKOK AREA - Srichuay, Jirayuth; Sasithanakornkaew, Saranthorn; Apisuphachok, Warapan (Journal of MCU Nakhondhat, 2023)
This research article aims to 1) study the consumers’ demographic characteristics, media exposure, marketing mix factors and their purchase intention of Inthanin coffee in Bangkok area. 2) study the relationship between consumers’ media exposure, marketing mix factors and their purchase intention of Inthanin coffee in Bangkok area 3) Study the influence of consumer’s media exposure, marketing mix factors and their purchase intention of Inthanin coffee in Bangkok area. This study used quantitative research design. This research methodology was conducted to study consumer’s behavior who experienced five branches Inthanin Coffee shop in which the exact number of samples was unknown. Therefore, a formula was applied to calculate the sample group of 400 people. The questionnaire was used as a data collection tool to analyze descriptive statistics, percentage, mean, standard deviation, hypothesis testing. The inferential statistical analysis was also adopted in this research together with the use of Pearson’s Product Moment correlation coefficient analysis and multiple regression analysis. The result of the study was found that the overall level of consumer’s media exposure of Inthanin coffee was moderate with a mean 3.34 The overall level of the marketing mix factors of Inthanin coffee was at a high level with a mean 3.93. And the overall level of their purchase intention of Inthanin coffee was also high with a mean 3.81. In testing the research hypothesis, the consumer’s media exposure and marketing mix factors had a positive correlation with consumers’ purchase intention of Inthanin coffee in Bangkok significantly. This statistical significance was at the 0.05 level and the marketing mix factors influenced the purchase intention of Inthanin coffee in Bangkok area the most (β = 0.47).